The Integration of 6Cs of the 21st Century Education into English Skills: Teachers’ Challenges and Solutions - Adani Shabrina; Utari Praba Astuti (Graduate School of Universitas Negeri Malang, 2022)
Abstract: In the 21st Century education, the 6 competencies are necessarily integrated into the classroom remembering the importance to complete students with better competencies. In line with the 6Cs integration, teachers’ challenges and solutions also need to be known. This study investigates English teachers’ challenges in integrating 6Cs of the 21st Century education into English integrated skills, and their solutions to cope with the challenges. This qualitative study elicited data from 20 English teachers through a questionnaire and an interview. The findings showed that students’ low motivation and poor vocabulary, time management, the difficulty in integrating some competencies and designing lesson plans were the challenges faced by teachers in integrating the 6Cs. Then, to cope with the challenges, teachers conducted group work and games, provided interesting videos, used a timer to manage the time, looked for references and discussed with other teachers to create lesson plans.Abstrak: Pada pendidikan abad ke 21, keenam kompetensi (6C) perlu diintegrasikan ke dalam kelas mengingat pentingnya melengkapi siswa dengan kompetensi yang lebih baik. Sejalan dengan pengintegrasian 6 kompetensi, tantangan dan solusi guru juga perlu diketahui. Penelitian ini menyelidiki tantangan yang dihadapi oleh guru bahasa Inggris dalam mengintegrasikan 6 kompetensi pendidikan abad ke-21 ke dalam keterampilan terintegrasi bahasa Inggris, dan solusi mereka untuk mengatasi tantangan tersebut. Studi kualitatif ini mengumpulkan data dari 20 guru bahasa Inggris melalui kuesioner dan wawancara. Hasil penelitian menunjukkan bahwa tantangan yang dihadapi guru yaitu kurangnya motivasi siswa dan kosakata Bahasa Inggris, manajemen waktu, kesulitan dalam mengintegrasikan beberapa kompetensi dan merancang rencana pelajaran. Untuk mengatasi tantangan tersebut, guru mengadakan kerja kelompok dan permainan, menyediakan video yang menarik, menggunakan pengatur waktu, dan mencari referensi sekaligus berdiskusi dengan guru lain untuk membuat rencana pembelajaran.